Callus induction and axillary shoot formation in Asparagus racemosus Willd. - Nabi, Neelofer; Singh, Seema; Saffeullah, Peer (Current Botany, 2020)
An experiment was performed to establish a regeneration protocol for an important medicinal plant, Asparagus racemosus. In the present investigation, nodal and internodal explants were employed for callus induction and axillary shoot formation. Maximum callus induction frequency was found on MS medium fortified with 2,4-D (1.0 mg/L) along with NAA (1.0 mg/L) and BAP (0.5 mg/L). However, individual effects of 2,4-D or NAA with BAP showed least callus induction. The higher concentrations of 2,4-D and BAP decreased the response of explants. However, maximum axillary shoot formation was observed on MS medium adjuvanted with BAP (2.0 mg/L) and NAA (0.5 mg/L).